Physiologic variations of serum tumor markers in gynecological malignancies during pregnancy: a systematic review - Han, Sileny N (BioMed Central, 2012)
BACKGROUND: Recent insights provide support for the treatment of cancer during pregnancy, a coincidence that poses both mother and fetus at risk. Our aim was to critically review studies on the physiologic variations during pregnancy, the most common tumor markers used in diagnosis and follow-up of gynecological cancers. METHODS: We conducted a systematic review of six tumor markers during normal pregnancy: carbohydrate antigen (CA) 15-3 (breast cancer); squamous cell carcinoma antigen (cervical cancer); and CA 125, anti-Müllerian hormone, inhibin B and lactate dehydrogenase (ovarian cancer). RESULTS: For CA 15-3, 3.3% to 20.0% of all measurements were above the cut-off (maximum 56 U/mL in the third trimester). Squamous cell carcinoma antigen values were above cut-off in 3.1% and 10.5% of the measurements (maximum 4.3 µg/L in the third trimester). Up to 35% of CA 125 levels were above cut-off: levels were highest in the first trimester, with a maximum value up to 550 U/mL. Inhibin B, anti-Müllerian hormone and lactate dehydrogenase levels were not elevated in maternal serum during normal pregnancy. CONCLUSION: During normal pregnancy, tumor markers including CA 15.3, squamous cell carcinoma antigen and CA 125 can be elevated; inhibin B, anti-Müllerian hormone and lactate dehydrogenase levels remain below normal cut-off values. Knowledge of physiological variations during pregnancy can be clinically important when managing gynecological cancers in pregnant patients.